PENGARUH KUALITAS LAYANAN DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH SERTA DAMPAKNYA TERHADAP LOYALITAS NASABAH (Studi pada Bank BRI Unit Balapulang Kabupaten Tegal) (Students' Journal of Economic and Management, 2015)
This study aims to measure the level of customer satisfaction and loyalty by examining variable that effect the identification of customer satisfaction and loyalty with Bank BRI Unit Balapulang. After a review of related literature, in this study determined significant variables that allegedly effect customer satisfaction and loyalty, which is variables quality of service that includes dimensions of of physical evidence, reliability, security, responsiviness and empathy and variable customer value can be seen as a basis for the development strategy of customer satisfaction leads to loyalty. Respondents were selected using purposive sampling technique. With a total sample of 100 customer Bank BRI Unit Balapulang. The data were analyzed using factor analysis to tes validity of the item in question, and the formula Croanbach’s Alpha to test the reliability of the instrumen. The data analysis technique used in this study was SPSS 19. Which is used to test the 3 (three) hypotheses that have been developed. The test results showed that the (1) quality of service to customer satisfaction showed a positive and significant, (2) the value to customers satisfaction showed a positive and significant influence, (3) customer satisfaction on customer loyalty showed positive and significant influence. Keywords: Service Quality, Customer Value, customer Satisfaction and Customer Loyalty